Cryoprotection–lyophilization and physical stabilization of rifampicin-loaded flower-like polymeric micelles - Moretton, Marcela Analía (2012)
Rifampicin-loaded poly(ε-caprolactone)-b-poly(ethylene glycol)-poly(ε-caprolactone) flower-like polymeric micelles display low aqueous physical stability over time and undergo substantial secondary aggregation. To improve their physical stability, the lyoprotection- lyophilization process was thoroughly characterized. The preliminary cryoprotectant performance of mono- and disaccharides (e.g. maltose, glucose), hydroxypropyl-β-cyclodextrin (HPβCD) and poly(ethylene glycol) (PEG) of different molecular weights was assessed in freeze-thawing assays at -20°C, -80°C and -196°C. The size and size distribution of the micelles at the different stages were measured by dynamic light scattering (DLS). A cryoprotectant factor (fc) was determined by taking the ratio between the size immediately after the addition of the cryoprotectant and the size after the preliminary freeze-thawing assay. The benefit of a synergistic cryoprotection by means of saccharide/ PEG mixtures was also assessed. Glucose (1 : 20), maltose (1 : 20), HPβCD (1 : 5) and glucose or maltose mixtures with PEG3350 (1 : 20) (copolymer:cryoprotectant weight ratio) were the most effective systems to protect 1 per cent micellar systems. Conversely, only HPβCD (1 : 5) cryoprotected more concentrated drug-loaded micelles (4% and 6%). Then, those micelle/ cryoprotectant systems that displayed fc values smaller than 2 were freeze-dried. The morphology of freeze-dried powders was characterized by scanning electron microscopy and atomic force microscopy and the residual water content analysed by the Karl Fisher method. The HPβCD-added lyophilisates were brittle porous cakes (residual water was between 0.8% and 3%), easily redispersable in water to form transparent systems with a minimal increase in the micellar size, as determined by DLS.